Antecedents of Organizational Citizenship Behavior of Human Resource Managers in the Public Sector - Asgari, Ali (2009)
The main purpose of this research was to determine the antecedents of organizational citizenship behavior of human resource manager s in the public sector. This study tested the direct and mediated models consisting of organizational citizenship behavior as the dependent variable. The independent variables included transformational leadership, transactional leadership, distributive justice, procedural justice, interactional justice, organizational tenure, organizational inflexibility, organizational formalization, task characteristic, individualistic behavior, collective behavior, and power distance. Leader member exchange, perceived organizational support, and trust in the manager were as the mediators. Two hundred and twenty staff from Iran and one hundred sixty two staff from Malaysia participated in this study. All the staff members were in the public sector. Results of the direct and mediated models revealed that there was a positive relationship between transformational and transactional leadership behavior; leader-member exchange, perceived organizational support, trust in the manager, task characteristics and organizational citizenship behavior among staff (managers and employees) in Iran and Malaysia. Leader-member exchange mediated the relationships between a) transformational leadership behavior, b) transactional leadership behavior, c) interactional justice and organizational citizenship behavior in Iran. However, in Malaysia, leader member exchange was not a mediator.